2016
DOI: 10.1021/acs.jafc.6b02716
|View full text |Cite
|
Sign up to set email alerts
|

Salt Taste Enhancing l-Arginyl Dipeptides from Casein and Lysozyme Released by Peptidases of Basidiomycota

Abstract: Some l-arginyl dipeptides were recently identified as salt taste enhancers, thus opening the possibility to reduce dietary sodium uptake without compromising palatability. A screening of 15 basidiomycete fungi resulted in the identification of 5 species secreting a high peptidolytic activity (>3 kAU/mL; azocasein assay). PFP-LC-MS/MS and HILIC-MS/MS confirmed that l-arginyl dipeptides were liberated when casein or lysozyme served as substrate. Much higher yields of dipeptides (42-75 μmol/g substrate) were rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 43 publications
0
26
0
1
Order By: Relevance
“…The highest amounts of both peptides were found after one week of cheese maturation, declining during further cheese ripening and this was independent of brine composition. No effect of salt reduction on the generation of these bitter peptides was found, but further analysis of the influence of salt reduction on proteolysis and the role of taste enhancing peptides (Harth et al ) should be done in further studies.…”
Section: Resultsmentioning
confidence: 96%
“…The highest amounts of both peptides were found after one week of cheese maturation, declining during further cheese ripening and this was independent of brine composition. No effect of salt reduction on the generation of these bitter peptides was found, but further analysis of the influence of salt reduction on proteolysis and the role of taste enhancing peptides (Harth et al ) should be done in further studies.…”
Section: Resultsmentioning
confidence: 96%
“…Hydrolysed vegetable and yeast proteins are flavour enhancers containing high levels of glutamate that also help initiate the umami taste. Partial replacement of salt with monosodium glutamate (<1.0%) did not result in negative sensorial properties of pork patties, although some studies [63] found high deterioration in quality, such as high cooking loss. Some of L-arginyl dipeptides were recently identified as salt flavour enhancers, in consequence, a possibility to reduce dietary salt intake without compromising palatability is raising [63].…”
Section: Possibilities Of Salt Reduction In Food Products By Reformulmentioning
confidence: 89%
“…DKPs can be used for preparation of supramolecular phase‐transfer catalysts and organo‐ and hydrogels, and may have a catalytic activity . DKPs can be used in the food industry as a substitute for salt . However, the taste of food can be spoiled due to the formation of cyclic dipeptides by cooking at high temperatures …”
Section: Introductionmentioning
confidence: 99%